Neonatal Birthmarks: A Prospective Survey in 1000 Neonates - Leelawadee Techasatian MD; Vilounna Sanaphay MD; Pongsatorn Paopongsawan MD; Lawrence A. Schachner MD (SAGE Publishing, 2019)
The majority of neonatal cutaneous conditions are benign and self-limited. However, some skin infections and specific birthmarks are serious and require proper management approaches. This study was a prospective survey of 1000 consecutive newborns at a tertiary care center in Northeast Thailand from September 2015 to 2016, which aimed to identify various cutaneous findings in newborns during their first 5 days of life. The authors found that Mongolian spots (66.7%) and sebaceous gland hyperplasia (60.9%) were the 2 most common cutaneous conditions found in the Thai population. Salmon patches were the most frequent vascular birthmarks (36%), followed by infantile hemangiomas (1.1%) and port wine stains (0.7%). Although majority of the neonatal cutaneous conditions are benign and self-limited, there were 8 cases (0.8%) of bullous impetigo in which both systemic and topical antibiotics were promptly prescribed.